2023
DOI: 10.1038/s41523-023-00522-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of A166, an antibody‒drug conjugate in advanced HER2-expressing solid tumours

Abstract: In this phase I study, the safety, pharmacokinetics, and antitumour activity of the HER2-targeted antibody–drug conjugate A166 were evaluated in patients with HER2-expressing advanced solid tumours. Patients with advanced solid tumours refractory to standard therapies received A166 at doses of 0.1, 0.3, 0.6, 1.2, 2.4, 3.6, 4.8 or 6.0 mg/kg Q3W in a standard “3 + 3” design. Dose cohorts were expanded at 4.8 and 6.0 mg/kg Q3W. Primary endpoints were assessment of the safety and tolerability of A166 and identific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Fifteen patients had previously received an anti-HER2 ADC other than T-DM1, including T-DXd. The ORR was 60% in these patients (9/15) [73] . A166 is another HER2-directed ADC composed of humanized HER2-targeting antibody linked to a cytotoxic drug (Duostatin-5, a microtubule inhibitor agent) via a stable cleavable linker.…”
Section: Next-generation Adcsmentioning
confidence: 80%
“…Fifteen patients had previously received an anti-HER2 ADC other than T-DM1, including T-DXd. The ORR was 60% in these patients (9/15) [73] . A166 is another HER2-directed ADC composed of humanized HER2-targeting antibody linked to a cytotoxic drug (Duostatin-5, a microtubule inhibitor agent) via a stable cleavable linker.…”
Section: Next-generation Adcsmentioning
confidence: 80%
“…Several novel anti-HER2 ADCs are under investigation, including A166, MM-302 and ARX788, that recently released some preliminary results from the early phase clinical trials. Allowing the exposure to previous ADCs, these trials contribute in part to shed a new light on ADC treatment sequencing [ 41 , 42 , 43 ]. Namely, A166 is a humanized anti-HER2 ADC conjugated with a novel anti-microtubule agent through a stable protease-cleavable linker, tested in pre-treated HER2-positve metastatic BC.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 1 studies revealed promising the efficacy and tolerable toxicity of A166 in HER-2-positive advanced solid tumors refractory to standard HER-2-targeted therapies [ 108 ]. There is another phase 1 trial currently ongoing in China in HER-2-overexpressing solid tumors (NCT05311397), but there are still no studies specifically in a breast cancer setting.…”
Section: Novel Her-2-targeted Therapiesmentioning
confidence: 99%